Taxonomy of 'Euconnus complex'. Part XIV. Diarthroconnus is removed from synonymy with Psomophus and placed as a junior synonym of Euconnus s. str. (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2017)
Diarthroconnus Ganglbauer, a subgenus of Euconnus Thomson, was proposed 117 years ago to accommodate one bizarre European species, E. birnbacheri Ganglbauer. Nine-segmented antennae with club composed of two terminal antennomeres was the main diagnostic character of the species and subgenus. Later authors interpreted this feature as a teratological abnormality, and E. birnbacheri as a junior synonym or an infraspecific taxon of E. intrusus Schaum. This led to listing Diarthroconnus as a junior synonym of Psomophus Casey in all existing catalogs, the latter being a subgenus of Euconnus to which E. intrusus belongs. However, since Ganglbauer's publication the type series of E. birnbacheri has not been studied and all taxonomic actions were results of interpreting his original description. Two syntypes of E. birnbacheri were recently rediscovered, and it was possible to clarify the status of Diarthroconnus. Euconnus birnbacheri was identified as identical with Euconnus (s. str.) fimetarius (Chaudoir), and consequently Diarthroconnus is removed from synonymy with Psomophus and placed as a junior synonym of Euconnus s. str. A lectotype is designated for Euconnus birnbacheri.